The mechanical properties of energetically deposited non-crystalline carbon thin films. (March 2016) - Kracica, M.; Kocer, C.; Lau, D.W.M.; Partridge, J.G.; Bradby, J.E.; Haberl, B.; McKenzie, D.R.; McCulloch, D.G.
Abstract: The mechanical behaviour of carbon films prepared with a variety of densities and microstructures was investigated using nanoindentation. Deposition energies between 25 and 600 eV and temperatures in the range 25–600 °C were used. Films prepared at low temperatures and moderate energies were amorphous with a high density. Finite element methods were used to model the stress fields, reproduce the indentation behaviour and evaluate elastic properties. Young's moduli up to 670 GPa and a low Poisson's ratio of ∼0.17 were found, comparable to polycrystalline cubic boron nitride, one of the hardest materials known. Films with the same density did not always show the same behaviour, emphasising the role of microstructure in determining mechanical response. Extended graphite-like regions within the films grown at high energy and high temperature, observed in transmission electron microscopy caused plastic deformation and failure to recover after a complete indentation cycle. At low deposition energies, the graphite-like regions were smaller in size causing plastic deformation but with complete recovery after indentation.